Evaluation of spring bread wheat accessions from the VIR collection for resistance to loose smut - M. M. Kovaleva; E. V. Zuev; A. N. Brykova (Труды по прикладной ботанике, генетике и селекции, 2019)
Background. Loose smut caused by Ustilago tritici (Pers.) Rostr. is one of the major diseases of wheat widespread in all areas of its cultivation. Breeding centers in Russia constantly need new sources of resistance to this disease. Screening of spring wheat accessions for resistance to loose smut has been carried out since 2016 in the Genetics Department of the N. I. Vavilov All-Russian Institute of Plant Genetic Resources (VIR) in collaboration with the Wheat Genetic Resources Department.Materials and methods. In the 2016-2018 growing seasons, new 139 accessions of spring bread wheat were screened for resistance to loose smut against a severe infection background according to the well-known method (Krivchenko, 1984). During wheat's flowering phase, from 7 to 10 ears of each accession were inoculated with a fungal infection collected on VIR's experimental field. The severity of the infection was determined by the disease symptoms on the susceptible reference cultivars: 'Reward', 'Diamant' and 'Scala'. Assessment of the infection lesions was carried out in the next year after inoculation by counting the diseased and healthy ears in each accession.Results and conclusion. The ears of eleven accessions were resistant to loose smut during two years of evaluation. During three years of evaluation the disease symptoms were not detected on the plants of eight accessions: 'Salavat Yulaev' (k-65560, Bashkortostan), 'Fori 4' (k-65592, Leningrad Province); 'Diablon' (k- 65444, Germany), 'Ke Feng 10' (k-65472, China), k-65479 (Algeria), k- 65482 (Turkey), 'Alikat' (k-65586, Canada) and 'Selection 1403' (k- 65828, USA). Three years of evaluation showed that 10 varieties were moderately resistant (no more than 5% affected ears): 4 from Russia, 2 from Canada, and single accessions from Spain, China, Pakistan and Tajikistan. The mentioned accessions are of interest for the development of spring bread wheat cultivars with resistance to loose smut for cultivation in the North-Western region of Russia.